2015
DOI: 10.1016/j.fuproc.2015.02.025
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary evaluation of ZSM-5/SBA-15 composite supported Co catalysts for Fischer–Tropsch synthesis

Abstract: a b s t r a c t a r t i c l e i n f oA series of ZSM-5/SBA-15 composite supported Co catalysts were prepared and evaluated for the Fischer-Tropsch synthesis (FTS) aimed to maximise the selectivity of C 5 -C 22 hydrocarbons in the product. The composite support was prepared by physically mixing ZSM-5 and SBA-15 of varying proportions and the finished catalysts had a constant Co loading of 15wt.%. The catalysts were tested for their performance in a high pressure fixed-bed reactor operating at T = 240°C, P = 2.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…[17,18]. García et al explored the effects of the Co-SiO2 interaction, and thought that SBA could suppress the aggregation of metal particles and promote the metal dispersion [19]. In this paper, the effect of the texture of Co/SBA-15 on FTS performance was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17,18]. García et al explored the effects of the Co-SiO2 interaction, and thought that SBA could suppress the aggregation of metal particles and promote the metal dispersion [19]. In this paper, the effect of the texture of Co/SBA-15 on FTS performance was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Cai et al and Wang et al reported that the CO conversion was 6.51%-20.51%, and C 5+ selectivity was 42.43%-77.14% when Ru promoted Co/SBA-15 catalysts was used in FTS [17,18]. García et al explored the effects of the Co-SiO 2 interaction, and thought that SBA could suppress the aggregation of metal particles and promote the metal dispersion [19].In this paper, the effect of the texture of Co/SBA-15 on FTS performance was investigated. Moreover, the reaction temperature and Co loading were also discussed.…”
mentioning
confidence: 99%
“…But with the addition of TiO 2 , the pore volume shows a ‘volcano’ type of trend with highest point for TS–TiO 2 ‐0.1, the same trend also being found in previous research . The reason may be attributed to the formation of new pores in the process of support accumulation . Similar to the corresponding supports, the Co‐loaded catalysts show the same changing tendency in pore volume.…”
Section: Resultssupporting
confidence: 80%
“…The reason may be the TiO 2 additive with lower surface area and larger pore diameter. But with the addition of TiO 2 , the pore volume shows a ‘volcano’ type of trend with highest point for TS–TiO 2 ‐0.1, the same trend also being found in previous research . The reason may be attributed to the formation of new pores in the process of support accumulation .…”
Section: Resultssupporting
confidence: 80%
“…Microporous zeolites with long‐path micropores have strong acidity, although they cause over‐cracking of hydrocarbons and give high selectivity to methane owing to the slow transportation of products to/from acidic sites . Furthermore, strong interactions between cobalt and pure zeolites usually cause low CO conversions . A recent study has attempted to synthesize large pore Co/zeolite bifunctional catalysts for FTS, such as mesopore/macropore zeolites .…”
Section: Introductionmentioning
confidence: 99%